Estudo geoarqueológico dos sítios do Rodo, Vau e Bispeira 8 - Monteiro-Rodrigues, Sérgio (2020)
The geoarchaeological studies carried out at Rodo, Vau and Bispeira 8 allowed to the recognition of three archaeological contexts associated with slope deposits that, in the first two cases, cover the surface of Pleistocene fluvial terraces, respectively, of the Vouga river and the Teixeira river. The slope deposits were controlled by small basins located at the top of the hills in the vicinity of the sites. Still with regard to Rodo and Vau, the main stage of slope erosion seems to coincide with the paleoclimatic event known as Dryas III. However, absolute dating and archaeological data showed that erosion also occurred after the Pleistocene. At Vau, Upper Paleolithic occupations were identified associated with flood deposits of the Teixeira river. More recent occupations are connected with local holocene colluvia. At Rodo, the main archaeological remains also date from the Upper Paleolithic, but the possibility of the existence of later occupations is not ruled out. At Bispeira 8, the remains of the human presence are less abundant and date mainly of the Upper Paleolithic and the Middle/Late Neolithic.